Quantitative proteomics reveals the effect of protein glycosylation in soybean root under flooding stress - Mustafa, Ghazala; Komatsu, Setsuko (Frontiers in Plant Science, 2014)
Flooding stress has a negative impact on soybean cultivation because it severely impairs growth and development. To understand the flooding responsive mechanism in early stage soybeans, a glycoproteomic technique was used. Two-day-old soybeans were treated with flooding for 2 days and roots were collected. Globally, the accumulation level of glycoproteins, as revealed by cross-reaction with concanavalin A decreased by 2 days of flooding stress. Glycoproteins were enriched from total protein extracts using concanavalin A lectin resin and analyzed using a gel-free proteomic technique. One-hundred eleven and 69 glycoproteins were identified without and with 2 days of flooding stress, respectively. Functional categorization of these identified glycoproteins indicated that the accumulation level of proteins related to protein degradation, cell wall, and glycolysis increased, while stress-related proteins decreased under flooding stress. Also the accumulation level of glycoproteins localized in the secretory pathway (e.g., peroxidases and plycosyl hydrolases) decreased under flooding stress. Out of 23 common glycoproteins between control and flooding conditions, peroxidases and glycosyl hydrolases were decreased by 2 days of flooding stress. mRNA expression levels of proteins in the endoplasmic reticulum and N-glycosylation related proteins were downregulated by flooding stress. These results suggest that flooding might negatively affect the process of N-glycosylation of proteins related to stress and protein degradation; however glycoproteins involved in glycolysis are activated.